1988
DOI: 10.1016/0165-1110(88)90020-6
|View full text |Cite
|
Sign up to set email alerts
|

Griseofulvin

Abstract: Griseofulvin (GF) is a mycotoxin produced by various species of Penicillium including P. griseofulvum Dierckx, P. janczewski (P. nigricans) and P. patulum. It is active against dermatophytic fungi of different species in the genera Microsporum, Trychophyton and Epidermophyton. Because of its capacity to concentrate in the keratinous layer of the epidermis and its relatively low toxicity in man, it has been extensively used in the therapy of dermatophytoses by oral administration. The biological activity of GF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 141 publications
1
35
0
1
Order By: Relevance
“…Griseofulvin, an orally active, nontoxic antifungal drug derived from several species of Penicillium, has been used for many years for the treatment of tinea capitis and other dermatophyte infections (36,37). Early studies showed that griseofulvin inhibits mitosis in sensitive fungi in a manner resembling the actions of colchicine (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Griseofulvin, an orally active, nontoxic antifungal drug derived from several species of Penicillium, has been used for many years for the treatment of tinea capitis and other dermatophyte infections (36,37). Early studies showed that griseofulvin inhibits mitosis in sensitive fungi in a manner resembling the actions of colchicine (21).…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro griseofulvin induces numerous chromosomal aberrations in all the systems analyzed (36). In mice and rats, prolonged treatment with griseofulvin provoked the development of multiple hepatomas (36).…”
Section: Discussionmentioning
confidence: 99%
“…Its mechanism of action has been thought to involve the selective inhibition of fungal cell mitosis in association with its accumulation in the keratin layers of the epidermis (1). Early studies demonstrated that griseofulvin inhibits mitosis in sensitive fungi in a manner resembling the actions of colchicine and other antimitotic drugs that act in mammalian cells by disrupting spindle microtubule (MT) function (3), although its precise mechanism of action in sensitive fungi remains unclear.…”
mentioning
confidence: 99%
“…Mitotic segregation is also induced in fungi by G F treatment. In higher eu karyotes, the cytostatic action o l'G F is essentially due to a mitotic arrest at late metaphase early anaphase [4]. G F .…”
Section: Introductionmentioning
confidence: 99%
“…Dietary ex posure to G F produced a significant incidence o f hepa tocellular tumors in mice, thyroid tumors in rats, but no carcinogenic activity in hamsters [12]. G F may also act either as a promoting or a carcinogenic agent, depending on the circumstances o f its administration [4], A cocarcinogenic effect on skin tumor development in mice was noted when G F was administered orally before, during or after topical treatment with methylcholanthrene [13][14][15].…”
Section: Introductionmentioning
confidence: 99%